Ulama methods in understanding verses mutasyabih (Study of the Tafwid and Ta'wil Methods Verses About the Attributes of Allah) - ade jamarudin; Nelvawita . (Jaqfi: Jurnal Aqidah dan Filsafat Islam, 2021)
In the realm of Islam, there is a recognized group that has a respectable place in the Muslim community. This group is the salaf group. Often every debate about the understanding of Islam is returned and a reference is sought which leads to that group. Knowing the application of the method of tafwid, taslim and ta'wil tafsili of salaf scholars in understanding the mutasyabihat verses about the nature of Allah SWT The understanding of the salaf ulama on the mutasyabihat verses in the future has an urgent relationship in the formation of the understanding of the firqah-firqah mentioned above. The great contradiction between the Musyabbihah and Ahlussunnah,. This research is in the form of literary research, meaning that this research will be directly based on written data in the form of books, especially classical works, as well as related books. From the development of the study of the Qur’an from the salaf period to the present day, it can be concluded that the study of the Qur’an has experienced rapid and dynamic developments and has passed through various eras, places and generations of thought. Although the description of the historical development of the Qur’an above is very limited and specialized in the scope of the early generation of intellectuals and that is not enough for all existing developments, this is sufficient to prove that the study of the Qur’an is never "dead" and obsolete. in the times